Evaluasi Kesiapan Puskesmas dalam Era JKN Terhadap Pemanfaatan Pelayanan Kesehatan Gigi dan Mulut di Kabupaten Timor Tengah Selatan - Maria Irena Faot; Yendris Krisno Syamruth; Fransiskus Geroda Mado; Anderias Umbu Roga; Imelda F.E Manurung (Malahayati Nursing Journal, 2026)
ABSTRACT Community Health Centers as primary healthcare facilities play an important role in supporting and improving public health including dental and oral health by providing high-quality healthcare services, particularly in delivering optimal services for communities within their working areas. Service quality is a key indicator influencing the community’s willingness to utilize healthcare services at Community Health Centers. This study aimed to analyze the readiness of Community Health Centers in the National Health Insurance toward the utilization of dental and oral health services in South Central Timor Regency. This study employed a quantitative research design and was conducted during February 2026. A total of 49 respondents were selected using a simple random sampling technique. Bivariate analysis using the Chi-Square test showed that there was no significant influence of the service system and regulations on service utilization (p = 0.366). However, there was a significant influence of the availability of healthcare personnel on service utilization (p = 0.049), the availability of facilities and infrastructure on healthcare service utilization (p = 0.039), and the availability of service types on healthcare service utilization (p = 0.012). Furthermore, multivariate analysis using ordinal regression demonstrated that the greater the readiness of facilities and infrastructure, the higher the utilization of healthcare services, while lower readiness in service types was associated with lower utilization. Overall, this study indicates that the service system and regulations had no significant influence on healthcare service utilization, while the availability of healthcare personnel, facilities and infrastructure, and service types significantly influenced the utilization of dental and oral health services. To improve the utilization of dental and oral health services at Community Health Centers in South Central Timor Regency, equitable distribution of healthcare personnel, adequate provision of facilities and infrastructure, and expansion of dental and oral healthcare service types are required. Keywords: Community Health Center Readiness, National Health Insurance, Dental and Oral Health Services. ABSTRAK Puskesmas sebagai fasilitas kesehatan tingkat pertama berperan penting dalam mendukung dan meningkatkan kesehatan umum termasuk kesehatan gigi dan mulut dengan memberikan pelayanan yang berkualitas tinggi, terutama dalam menyediakan pelayanan yang optimal bagi masyarakat di wilayah kerjanya. Kualitas pelayanan menjadi indikator utama agar masyarakat mau mengakses pelayanan kesehatan di puskesmas. Penelitian ini bertujuan untuk menganalisis kesiapan puskesmas di era JKN terhadap pemanfaatan pelayanan kesehatan gigi di Kabupaten Timor Tengah Selatan. Jenis penelitian ini adalah kuantitatif, dilakukan selama bulan Februari 2026, jumlah sampel 49 responden dipilih dengan teknik simple random sampling. Uji bivariat menggunakan Chi-Square yang diperoleh tidak ada pengaruh system pelayanan dan regulasi terhadap pemanfaatan pelayanan dengan p=0.366, ada pengaruh ketersediaan tenaga kesehatan dengan pemanfaatan pelayanan p=0.049, ada pengaruh ketersediaan sarana prasarana terhadap pemanfaatan pelayanan kesehatan p=0.039 dan ada pengaruh ketersediaan jenis pelayanan terhadap pemanfaatan pelayanan p=0.012. Sementara itu multivariat menggunakan regresi ordinal hasilnya menunjukkan semakin siap ketersediaan sarana prasarana semakin tinggi pemanfaatan pelayanan kesehatan, semakin tidak siap ketersediaan jenis pelayanan semakin rendah pemanfaatan pelayanan kesehatan. Secara keseluruhan penelitian ini menunjukkan tidak ada pengaruh system pelayanan dan regulasi terhadap pemanfaatan pelayanan kesehatan dan ada pengaruh ketersediaan tenaga kesehatan, sarana prasarana dan jenis pelayanan terhadap pemanfaatan pelayanan kesehatan. Untuk meningkatkan pemanfaatan pelayanan kesehatan gigi dan mulut puskesmas yang ada di Kabupaten Timor Tengah Selatan perlu adanya pemerataan tenaga kesehatan, perlu adanya pemenuhan ketersediaan sarana prasarana dan penambahan jenis pelayanan kesehatan gigi dan mulut di puskesmas. Kata Kunci: Kesiapan Puskesmas, Jaminan Kesehatan Nasional, Pelayanan Kesehatan Gigi dan Mulut.